Economic benefits of rational perennial planting use under global climate change in Chuy - Belek uulu Esenbek; Rakhmatova Mavliuda; Ibraeva Nurila; Shakirova Klara; Chortonbaeva Asel; Ishekeev Nazarkul (BIO Web of Conferences)
The article examines the economic efficiency of using perennial plantings in the context of global climate change using the example of farms in the Chui region. The analysis is based on data on the current use of agricultural technologies and modeling their impact on economic benefits. The study highlights opportunities to adapt and optimize agricultural practices in response to climate challenges, discussing both traditional and innovative approaches to managing perennial crops. Particular attention is paid to sustainable practices that increase productivity and minimize environmental impact. The results of the study offer specific recommendations for farmers and agronomists, and also highlight key directions for policymakers in the field of agricultural policy and the environment.